Direct and indirect effects of component traits on soybean seed yield under seasonal variation (Bangladesh Journal of Botany, 2025)
Soybean is a quantitative short-day plant, which restricts its cultivation to the rainy season in India. But due to increasing demand for soybean oil and protein-rich products, the farmers are cultivating in off-seasons also. A study of fifteen soybean genotypes during rainy, post-rainy and summer seasons differing in photoperiod and temperature regimes indicated differential association between yield components and yield in different seasons. Plant height exhibited a significant positive correlation with seed yield during the post-rainy season but non-significant during rainy and summer seasons. A high positive direct effect of the number of branches per plant and the number of seeds per pod was observed during the rainy season while the number of pods per plant and hundred-seed weight were observed during the summer. Days to maturity exhibited high positive direct effect on seed yield across the seasons. The study highlights the necessity to prioritize selection strategy on days to maturity while breeding soybean varieties suitable for all three seasons.Bangladesh J. Bot. 54(3): 441-446, 2025 (September)